Teachers' Efforts in Improving Children's Learning Disability - Anggriana, Triana Widya Anggriana (Angstrom Centre of Education, 2022)
This study aims to determine the services of children with special needs in terms of identification, assessment and curriculum development models carried out by elementary schools. The method used in this study is a qualitative descriptive method. The subjects in this study were one teacher and one student with special needs, namely students with difficulties studying at SDN Babakan Jawa III, Majalengka District, Majalengka Regency. This research procedure includes three stages, namely: the pre-field stage, field implementation, and the member check stage and then data analysis is carried out. This study explained the initial identification activities of students with learning disabilitie using special identification tools for children with special needs then continued with assessment activities. From this, obtaining information related to the ability of students to have learning difficulties from the aspect of reading the beginning and subsequently used in the provision of educational services. The curriculum development model applied is a modification of the curriculum according to the abilities of the child. This activity is still experiencing obstacles because the facilities and infrastructure to support learning for students with learning difficulties are not yet available, besides that the resources are not ready.